2013
DOI: 10.6000/1929-4247.2013.02.04.2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Factors Influencing Preterm Birth and Low Birth Weight in Oman: A Hospital Based Study

Abstract: Background: Preterm births (PTB) and low birth weight (LBW)-the two distinct adverse pregnancy outcomesare the major determinants of perinatal survival and development. The purpose of this study was to determine the incidence of LBW and PTB and identify the maternal and neonatal risk factors influencing them. Methods: Data for the study come from a cross-sectional retrospective study conducted at the maternity ward of Sultan Qaboos University Hospital (SQUH) in Oman during the period between November 2011 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…24 In the region, the study from Oman have examined 534 singleton live births for maternal and neonatal factors influencing preterm birth and LBW in Oman and found the incidence of LBW at13.7%. 6 Oman is a border country to Yemen, and relatively, has well established health system and better living conditions. The current study had revealed significant findings related to the following factors; rural residences (P<0.012); 19-30 maternal age group (p<0.026); poor socio-economic status (p<0.031); no ante-natal care (p<0.030); maternal anaemia (p<0.005); maternal under-nutrition (p<0.001); gestational age less than 37 weeks (p<0.001); use of family planning services (p<0.046) and time to nearest health facility (p<0.005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In the region, the study from Oman have examined 534 singleton live births for maternal and neonatal factors influencing preterm birth and LBW in Oman and found the incidence of LBW at13.7%. 6 Oman is a border country to Yemen, and relatively, has well established health system and better living conditions. The current study had revealed significant findings related to the following factors; rural residences (P<0.012); 19-30 maternal age group (p<0.026); poor socio-economic status (p<0.031); no ante-natal care (p<0.030); maternal anaemia (p<0.005); maternal under-nutrition (p<0.001); gestational age less than 37 weeks (p<0.001); use of family planning services (p<0.046) and time to nearest health facility (p<0.005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified that the incidence rates in Asia; range from 5.2% to 30%, sub-Saharan Africa; range from 7% to associate with LBW outcomes. [6][7][8][9][10][11][12] In Yemen, LBW has been documented as a public health concern and one study has found that younger mothers and bleeding during pregnancies are more likely to produce LBW but however, very little are known about the association of LBW with maternal nutrition status. 13,14 Evidences from the world have indicated significant association of maternal under-nutrition and LBW, reinforces the importance of good nutrition for mothers in reducing child and maternal illnesses and deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Regular antenatal care will prevent, detect and treat factors which negatively affect the baby also it provide advices and health education about food, supplementation and effect of smoking and alcohol [12],also small sample size of our study may had role in our result. Another study done in Oman, found that ANC visits significantly independent to the LBW [18], while two studies done in Bangladesh showed that there is a significant relationship between ANC visits and birth weight (p<0.001, OR=29.386) (p=0.001) (20,23). Our study assessed the use of supplementation during pregnancy and we found that 66.5% of the cases took their supplementation regularly while 70% of control did this means most of the study population has regular supplementation of iron, folic acid and calcium, this may be explained by their regular ANC but at the end there is no statistically significant relationship with LBW (P= 0.237).This may be explain by in our study we exclude babies with congenital anomalies as we know folic acid prevent congenital anomalies like neural tube defect (12,20,21).We had two studies first one found that the risk of VLBW was decreased sevenfold with a 1 st trimester use and six fold when prenatal supplements were used in the 2 nd trimester [2],the other study in rural Gambia found that the use of prenatal supplements significantly increased birth weight, particularly during the nutritionally debilitating hungry season (June to October).…”
Section: Discussionmentioning
confidence: 95%
“…Antenatal care is found to be one of the factors associated with LBW as the more visits the more heath education, the more screening for complication and the more supplement given. In Oman there was study which found that 15.1 % of women who had less than 4 ANC visits have LBW infant and 84.9 % of women who had more or equal than 4 ANC visits have LBW infant [18]. Conversely another study found out that women who had poor quality antenatal care the percentage of LBW was 39.8 % and women who had Licensed Under Creative Commons Attribution CC BY average quality antenatal care the percentage of LBW was 60.1 % (P<0.001) [16].…”
Section: Literature Reviewmentioning
confidence: 98%
“…5, 15, 16, 18-24, 28 Statistical tests, such as the t test, were applied in some studies to draw inferences. 14, 17, 23, 24…”
Section: Introductionmentioning
confidence: 99%